Brood size and its importance for nestling growth in the Biscutate Swift (Streptoprocne biscutata, Aves: Apodidae) - M. Pichorim (Brazilian Journal of Biology)
Many Apodidae, including Streptoprocne biscutata (Sclater, 1866), drop eggs from their nests during incubation. This is interpreted as nest site competition or accident. We provide evidence that egg ejection is deliberate and that this behaviour controls the brood size. Brood sizes were manipulated and nestling growth was measured to test the hypothesis that pairs can regulate brood size during incubation based on current ability to rear nestlings. Natural (control) broods with one, two and three nestlings, and manipulated (experimental) broods reduced to one and increased to two and three young were monitored. Growth rates were measured based on weight, and wing, tail and tarsus lengths of natural and manipulated broods. We compared the slopes of each measure's regression lines of the nestlings of each brood size by t-test. Nestling growth of control nests was similar and relatively little associated with brood size. In broods reduced to one nestling, weight, wing and tail had greater growth rates, and in broods increased to three nestlings growth rates were lower. Weight was most, and tarsus length least influenced by brood size. In general, nestling growth of manipulated nests was inversely proportional to brood size. The results suggest that pairs with larger clutches are in better physical conditions than others. Thus, in experimental broods, pairs are over or under-loaded because feeding activities increase or decrease and these changes affect the growth rate of the nestlings. The present study suggests that egg ejection can control brood size. This behaviour is probably stimulated by physical changes in the adult birds during incubation.